Penyuluhan dan Rehabilitasi Hutan Mangrove dalam Upaya Mencegah Bencana Banjir di Perairan Desa Waiheru - Nur Alim Natsir; Asyik Nur Allifah AF (IAIN AMBON, 2022)
The Mangrove Ecosystem is an ecosystem that has unique and distinctive characteristics. The potential for biodiversity that has attracted all groups to take advantage of it so that the population and diversity is reduced. Awareness of the importance of mangrove ecosystems is not fully owned by the community due to several factors including knowledge about the role of mangroves in life and solutions to restore mangrove populations. The service program is carried out in collaboration with the Maritime Zone Marine Security Agency (BAKAMLA) of the Ambon Maritime Zone and the Waiheru Village community. The purpose and benefits of this service activity are to provide counseling about the importance of maintaining coastal ecosystems, especially mangroves, provide knowledge about how to plant mangroves, build public awareness to pay more attention to the environment and maintain ecosystems, one of the activities that can preserve the balance of the mangrove ecosystem, and provide knowledge to the community. students who are directly involved in the mangrove planting process. The methods used include counseling and planting mangroves in beach of Waiheru Village, Ambon. The results of the service show the extraordinary attention of the community with the planting of mangroves and the message of the importance of mangroves on the coast is conveyed so that it changes people's behavior so that they always protect the coastal environment and utilize mangroves by not exceeding the limit. Keywords: mangrove, coastal, ecosystem, BAKAMLA, population